Open Total Talus Dislocation: A Case Report - Tan, E (Malaysian Orthopaedic Association, 2012)
ABSTRACT: Total talus dislocation is a rare injury and is commonly accompanied by associated fractures. Common worrisome sequelae are infection, avascular necrosis and post-traumatic arthritis. We report here on a patient who sustained an open total talus dislocation with an ipsilateral medial malleolus fracture. Following early debridement, reduction and a combination of internal and external fixations, early recovery was good with no evidence of avascular necrosis. KEY WORDS: Total talus dislocation, avascular necrosis, infection, outcome